Anticoagulation Management and Monitoring during Pediatric Extracorporeal Life Support: A Review of Current Issues - Ryerson, Lindsay M.; Lequier, Laurence L. (Frontiers in Pediatrics, 2016)
Anticoagulation is an imperfect science and is even more complicated in neonates and young children. The addition of the extracorporeal life support (ECLS) foreign circuit adds an additional layer of complexity. Anticoagulation goals during ECLS are to maintain a clot-free circuit and a hemostatically balanced patient. Unfractionated heparin (UFH) is the default gold standard anticoagulant as no large studies have been performed on any other anticoagulants. This review will focus on the advantages and disadvantages of the various methods to monitor UFH anticoagulation, discuss alternative anticoagulants, and examine bleeding and thrombotic complications during ECLS.